Unraveling the stable green super rice lines across the multi-environment yield trials - Ullah, Mati (Pakistan Journal of Agricultural Sciences, 2023)
The aim of this study is to understand molecular characterization and antimicrobial resistance of diarrheagenic and nondiarrheagenic E. coli from healthy and diseased farm fish from Cypriniformes order. A total of 516 healthy and diseased farmed fish samples belong to Cypriniformes order were collected from various regions of Punjab and screened for E. coli. Biochemical tests and PCR confirmation were conducted using the 16S rRNA and UspA genes. DEC was examined through PCR using different virulence genes. All isolates were tested for various antibiotics using the disk diffusion method. The phenotypic and genotypic resistances of Extended-spectrum β-lactamases (ESBLs) were investigated. A Chi-square test was performed to compare the prevalence of E. coli, virulence genes, and ESBLs genes with a significance level of P ≤ 0.05. Out of the total fish samples, 16.66% and 36.57% of E. coli strains were confirmed through biochemical tests and PCR, respectively. The DEC pathotypes were recorded in 30% and 62.02% of isolates from healthy and diseased fish, respectively. A higher rate of 19.37% of EAEC pathogroup was observed in both healthy and diseased fish, while the EIEC pathogroup was only observed in diseased fish at a rate of 10.07%. The significance (P ≤ 0.05) was observed among the virulence genes. The highest resistance rates among diarrheagenic and non-diarrheagenic strains were observed with tetracycline, amoxicillin, and ceftazidime. A higher prevalence of CTX-M (56.81%) and TEM (43.18%) was recorded in DEC pathotypes, while blaSHV was not detected. The high prevalence of DEC E. coli, and the production of ESBLs, indicate unhygienic practices and the misuse of antibiotics in fish farms.